1991
DOI: 10.1099/00221287-137-2-323
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose-6-phosphate synthase/phosphatase complex from bakers’ yeast: purification of a proteolytically activated form

Abstract: Journal of General Microbio/ogyA protein of about 800 kDa with trehalose-6-phosphate synthase (TPS) and trehalose-6-phosphate phosphatase (TPP) activity was purified from bakers' yeast. This TPS/P complex contained 57,86 and 93 kDa polypeptides. The 86 and 93 kDa polypeptides both appeared to be derived from a polypeptide of at least 115 kDa in the native enzyme. A TPS-activator (a dimer of 58 kDa subunits) was also purified. It decreased the Michaelis constants for both UDP-glucose (three-fold) and glucose 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 24 publications
2
45
1
1
Order By: Relevance
“…Gel filtration experiments showed that the molecular mass of the complex is around 630-800 kDa (Londesborough and Vuorio, 1991;Bell et al, 1992). As the sum of the molecular masses of the four putative subunits only adds up to Ϸ400 kDa, either some or all of the subunits must exist in more than one copy in the complex.…”
Section: Discussionmentioning
confidence: 99%
“…Gel filtration experiments showed that the molecular mass of the complex is around 630-800 kDa (Londesborough and Vuorio, 1991;Bell et al, 1992). As the sum of the molecular masses of the four putative subunits only adds up to Ϸ400 kDa, either some or all of the subunits must exist in more than one copy in the complex.…”
Section: Discussionmentioning
confidence: 99%
“…TCT AAG GGC AAT ATC GTT TAC ATC ATG AAC TCA TTT CCA AAG CCC ATT CTG GAA AAT CTT TAC AGT CGT GTG CAA seemed to result from the adventitious truncation of the 123-kDa polypeptide during the purification (Londesborough and Vuorio, 1991), we attempted to convert the intact enzyme into the truncated form by treatment with trypsin. Fig.…”
Section: Truncation Of Intact Trehalose Synthase With Trypsin Causingmentioning
confidence: 99%
“…The 56-kDa, 86-kDa and 93-kDa polypeptides of truncated trehalose synthase were separated by SDSPAGE, digestejd on nitrocellulose blots and fractionated by HPLC as described in Londesborough and Vuorio (1991). These polypeptides and polypeptides of molecular mass 56, 102 and 123 kDa, immunoprecipitated with anti-(trehalose synthase) serum from high-speed supernatants of yeast extracts, were also separated by SDSPAGE and digested in the gel with lysylendopeptidase C. The derived peptides were separated by HPLC using a DEAE-cellulose pre-column before the reverse-phase column essentially as described by Kawasaki and Suzuki (1990).…”
Section: Sequencing Of Peptidesmentioning
confidence: 99%
See 2 more Smart Citations